Meet the Romans : presented by Mary Beard : as seen on BBC - Beard, Mary, 1955- ([s.l.] : Lion Television Limited, 2012)
Thema-dvd - Three-part history series about life in Ancient Rome presented by classicist Mary Beard. The programmes look at the effect of the Empire on the everyday Roman, visiting notable sites such as the Colosseum and Monte Testaccio and exploring the lives of real citizens from the time. The episodes comprise: 'All Roads Lead to Rome', 'Streetlife' and 'Behind Closed Doors'. - Romeinse Tijd - Het oude Rome